Application of Constraint-Induced Movement Therapy (CIMT) to Improve Upper Extremity Motor Skills for Hemorrhagic Stroke Patients - Ramadhani, Arini Kartika; Pompey, Cut Sarida (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2026)
One of the main complications that often arises from hemorrhagic stroke is hemiparesis, which is weakness on one side of the body resulting in a significant decline in upper extremity motor function. This condition makes it difficult for patients and causes them to lose their independence in performing daily activities. Rehabilitation through adjunctive therapy is essential for restoring motor function, and one such therapy is Constraint-Induced Movement Therapy (CIMT). This therapy is performed by restricting the movement of the healthy limb to stimulate the weaker side to be used more actively. The purpose of this case study is to analyze the application of nursing care for hemorrhagic stroke patients with CIMT therapy interventions in an effort to improve upper extremity motor function. Therapy was administered to two patients for three consecutive days, twice a day, with each session lasting 20 minutes. The therapy results were evaluated using the Fugl-Meyer Assessment Upper Extremity (FMA-UE) and the Chedoke Arm and Hand Activity Inventory-9 (CAHAI-9) instruments. The results showed an increase in FMA-UE and CAHAI-9 scores after the therapy, the FMA-UE score increased from 29 to 46 in Mrs. J and from 39 to 46 in Mrs. Y. The CAHAI-9 score also increased from 20 to 36 in Mrs. J and from 32 to 48 in Mrs. Y, indicating improved upper extremity motor function. CIMT therapy has been proven effective in improving motor function and independence in post-stroke patients. Further research is expected to examine the effectiveness of CIMT on sensory function and quality of life in patients.